USUÁRIO INFANTIL E EBOOK: UM OLHAR PARA O PORTAL BIBLON - Reis, Edilson Thialison da Silva (2016)
With the increasing amount of websites for digital literary Reading, has shown a clear need for a study focused in these tools. The research subject is the Portal Biblon , social network addressed to children users, which has to promote reading through literary narratives, adding users around the literary text. The research analyzes E-books´ graphic interfaces available on this website under the editorial design guidelines emphasized on the Child user´s experience. Based on interaction and editorial design, analyzes the main features of an E-book for children users. Applying the research methodology with qualitative approaching, it was noted that the Editorial Design´s elements work as inspirational parameters for reading and when an E-book is not designed taking into account the need of its target audience, it works as an opposite element of its function, that is, instead of encouraging the reading, causes frustration and a lack of interest in it.